2022
DOI: 10.1371/journal.pone.0264142
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between benevolent leadership and affective commitment from an employee perspective

Abstract: Benevolent leadership has emerged as a contemporary leadership style that has been studied only scantly. To fill this gap, this work has two goals. The first is the identification and assessment of the relationship between benevolent leadership and employees’ affective commitment in the context of Polish organizations. Secondly, it will be investigated whether all constructs of benevolent leadership contribute to affective commitment. Data were obtained from 415 company employees. The relationships were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 98 publications
1
2
0
1
Order By: Relevance
“…Our results suggest that head nurses’ benevolent leadership can increase nurses’ commitment levels toward the hospital where they work. This finding is consistent with previous research that also reported a positive relationship between benevolent leadership and affective commitment [ 41 , 42 ]. However, what this paper differs from the previous studies is that we found a positive relationship between benevolent leadership and affective commitment in the context of nursing rather than the normal organizations.…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that head nurses’ benevolent leadership can increase nurses’ commitment levels toward the hospital where they work. This finding is consistent with previous research that also reported a positive relationship between benevolent leadership and affective commitment [ 41 , 42 ]. However, what this paper differs from the previous studies is that we found a positive relationship between benevolent leadership and affective commitment in the context of nursing rather than the normal organizations.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, ethical leaders play a pivotal role in shaping corporate cultures that prioritise and uphold the principles of data privacy. Leadership that exhibits a steadfast dedication to ethical practises in the management of information and data serves as a model for fellow employees (Grego-Planer, 2022). This cultivates a conducive atmosphere wherein team members are encouraged to confidentially disclose security breaches, engage in deliberations regarding ethical dilemmas, and actively contribute to data-driven decision-making processes.…”
Section: Resultsmentioning
confidence: 99%
“…First, this study extends the organizational commitment literature and the application of social exchange theory by empirically revealing the linkage between governance mechanisms and organizational commitment in the context of cooperatives. While previous studies have extensively explored the influencing factors of organizational commitment using social exchange theory [ 57 ], most of them have focused on investor-owned firms and overlooked the role of governance mechanisms in shaping organizational commitment. The unique characteristic of cooperatives lies in the fact that their members are the main owners, managers, and patrons [ 13 ].…”
Section: Discussionmentioning
confidence: 99%